A 5-Year-Old Male Child With Late Infantile Metachromatic Leukodystrophy: A Case Report. (March 2015) - Mahmood, Afreen; Chacham, Swathi; Reddy, Uppin Narayan; Rao, Jillalla Narsing; Rao, S. Pratap
Metachromatic leukodystrophy is a rare disorder of myelin metabolism. This degenerative disorder results from the accumulation of cerebroside sulfatide within the myelin sheath of central and peripheral nervous system, due to deficiency of aryl sulfatase A enzyme. We report a 5-year-old male child, who presented with regression of milestones, recurrent seizures and spasticity from second year of life. Initially neurodegenerative disorder was considered and the case was investigated with neuroimaging and enzyme levels. Computed tomography (CT) of the brain showed hypodensities in the corpus callosum and bilateral periventricular and deep cerebral white matter suggestive of neurodegenerative disorder. Subsequently, magnetic resonance imaging (MRI) of the brain was done, which showed symmetrical hyperintensities in the periventricular white matter with classical sparing of subcortical "U" fibers. The β-galactosidase enzyme activity was normal; however, the activity of aryl sulfatase A enzyme was undetectable, confirming the diagnosis of late infantile variant of metachromatic leukodystrophy.